Dinamika Persenjataan di Asia Tenggara, 2010-2015 - Iwan Sulistyo (Andalas Journal of International Studies (AJIS), 2017)
States, however, are still the main actors in International Relations. Although the Cold War had formally ended in 1991, as a matter of fact, the military competition still exists, including at the regional level. This article attempts to analyze the arms dynamic in Southeast Asia during the 2010-2015 periods. By using three models – action-reaction model, the domestic structure model, and the technological imperative – simultaneously and analyzing the data published by both the IISS and SIPRI, this study shows that conflict in the South China Sea had been the primary motive of several countries in increasing their military spending and enhancing their military capabilities, both qualities as well as quantities. Several countries accelerating their military strength had been Singapore, Malaysia, Vietnam, the Philippines, Myanmar, Thailand, and Indonesia. However, Singapore had been the leading actor that has significant efforts in strengthening its military power. Relizing the difficulty to identify the actual motives of these several countries enlarging their hard power, the author argues that, within this arms dynamic, there is also a possibility or even the long-term tendency in terms of arms race as long as these major actors that relates directly to the South China Sea territorial conflict are not able carefully to maintain their security dilemma and perceived threats.  Kata Kunci: Arms dynamic, Southeast Asia, military capability